Hypoleptinaemia in patients with anorexia nervosa and in elite gymnasts with anorexia athletica - Matejek, N.; Weimann, E.; Witzel, C.; Molenkamp, G.; Schwidergall, S.; Bohles, H. (International Journal of Sports Medicine, 1999)
Leptin, the product of the ob-gene, is specifically released by adipocytes. In addition to its metabolic function it seems to affect the feedback-mechanisms of the hypothalamic-pituitary-gonadal-axis. We studied 13 female juvenile elite gymnasts with anorexia athletica (AA) and 9 female patients with anorexia nervosa (AN) regarding the relation between leptin, fat stores, and the reproductive hormone levels. Leptin levels in females with anorexia nervosa (Tanner stage B4 [median]; mean age: 17.8 +/- 1.7 years) were low (2.9 +/- 2.7 microg/L), and were related to body mass index (BMI) (r = 0.71; p = 0.03) and percentage body fat mass (r = 0.78; p = 0.01). Leptin levels of the elite gymnasts were even more decreased (1.2 +/- 0.8 microg/L) caused by the low amount of fat stores. Leptin correlated with BMI (r= 0.77; p = 0.004) and the percentage body fat mass (r = 0.6; p = 0.04). In elite gymnasts leptin levels correlated with CA showing an age-dependent increase (r= 0.59; p = 0.04). Oestradiol was secreted at a low level in both groups (AN: 25.6 +/- 17.4 microg/L; AA: 24.4 +/- 13.5 microg/L). A delay in menarche and a retarded bone maturation occurred in AA. Our results clearly show that leptin levels are low in restrained eaters. Leptin levels represent the fat stores in the body and play a permissive role for female pubertal development. There is evidence that the mechanisms leading to a dysregulation of the reproductive-axis in patients with AN are comparable with those leading to delayed puberty in juvenile elite gymnasts with AA. This implies that AN and AA are overlapping groups and AA can lead to the development of AN.